Kajian Literatur : Perlindungan Hukum Terhadap Korban Revenge Porn (Doktrin: Jurnal Dunia Ilmu Hukum dan Politik, 2024)
Gender inequality, sexual violence, domestic violence, trafficking in women, and wartime exploitation are some of the many human rights violations that occur. With the advancement of information technology and globalization, the use of violence has changed and evolved. Revenge pornography, also known as "revenge porn", is combined with direct acts of violence. The purpose of this research is to find out what causes revenge pornography and how legal protection can be given to its victims. This research uses normative research that uses legislation to examine a study by examining theories, concepts. Some of the causes of revenge pornography crimes are as follows: Ineffective laws, the patriarchal culture that still exists in Indonesian society, lack of sexual education, law enforcement that has not run properly, and handling victims who often backfire. The state is responsible for protecting victims of sexual harassment. Several existing laws protect victims of pornographic abuse.